Youth Policies in Europe: big changes after the big crisis? An explorative analysis - Guidi, Riccardo (SocietàMutamentoPolitica, 2015)
The paper deals with current innovation trajectories in European youth policies. It is aimed at exploring European Union policy addresses on youth condition and the youth policies of four EU Member Countries (Germany, Denmark, United Kingdom, Italy) belonging to different welfare and youth transition regimes. Although the analysis is explorative and the results must be considered preliminary only, a minimalist and workfare-based policy approach seems to characterize European youth policies in times of crisis. This confirms that social changes are not enough per sé to generate policy interventionism. The European relative political inertia against the hard effects of post-2008 crisis risks to further strengthen inequalities among social groups, age groups and countries.